امتداد الأنا في العالم مقاربة سيميائية في التجربة الصوفية عند الشاعر عبد الله العشي - بشلاغم, سلام (كلية الأدب العربي والفنون, 2025)
يُـــعَدّ موضوع التّصوّف من المواضيع الحداثية التي لاقت اهتماما كبيرا في الأدب عموما والشّعر على وجه الخصوص ، حيث ركّز عليه الشّعراء المعاصرون لانزياحه الى الطّابع الرّوحانيّ الذي يستند الى التّجربة الصّوفيّة الخاصّة بالشاعر الذي يحمل هذا الفكر ، فلجأوا الى الرّمزية والغموض لبناء شخصيّة فكريّة تساعد على فهم الحقيقة المطلقة التي يمتدّ فيها الأنا في العالم كما عبّر عنها الشّاعر الجزائريّ المعاصر عبد الله العشّي من خلال تجربته الشّعريّة في التّصوّف The subject of Sufism is considered one of the modern topics that has garnered significant attention in literature in general and poetry in particular. Contemporary poets have focused on it due to its spiritual nature, which is based on the Sufi experience of the poet who embodies this thought. They resorted to symbolism and ambiguity to build an intellectual character that helps in understanding the absolute truth, where the self extends into the world, as expressed by the contemporary Algerian poet Abdullah Al-Ashi through his poetic experience in Sufism
Keywords: التّصوّف، التجربة الصّوفيّة ،الامتداد ،الانا ،العالم ، عبد الله العشّي; Sufism, the Sufi experience, extension, the ego, the world,Abdullah Al-Ashi.